Stanislaw Jundzill: A Propagator of Naturalistic Ideas - Griška, Albinas (Problemos, 1971)
St. Jundzill (1761-1847), a professor of botany and zoology at the old Vilnius University, was the first chief of the chair of botany. His main field was taxonomy. St. Jundzill combined his scientific and teaching activities with the practical work in the botanical gardens, the founder of which he himself was. He wrote many works. “A Course in Zoology” (1807), “Foundations of Botany” (1818) were the first manuals both for students of the University and pupils of secondary schools. Besides, he wrote many popular booklets and articles for the public at large. St. Jundzill’s treating of life phenomena depending on some original spiritual principle was limited to mental activity, thinking. His reasoning, however, suggests the conclusion that even the functioning of the latter is determined by natural processes going on in the organism apart from which it could neither exist nor manifest itself. St. Jundzill had rejected the doctrine of prereformism and defended the thesis of the individual development of organisms thereby supporting a more progressive theory of epigenesis. Besides, adherent to the constancy teaching as he was, Jundzill sometimes would come close to the theory of species that was then in the making.